2000
DOI: 10.1016/s1010-7940(00)00591-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sparing thoracotomy: a biomechanical analysis confirms preservation of muscle strength but no improvement in wound discomfort

Abstract: All thoracotomy patients have long term wound related symptoms. This situation is not improved by performing a muscle sparing incision. However thoracotomy through the triangle of auscultation can preserve latissimus dorsi strength which is compromised in a posterolateral thoracotomy incision. We therefore recommend that a muscle sparing thoracotomy be considered for patients where preservation of muscle strength is deemed important, providing the operation is not compromised due to inadequate access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Two retrospective studies found no difference between the classic posterolateral approach and the musclesparing posterolateral approach. 15,16 A subanalysis from a prospective study also found no difference in PTPS based on incision type. 17 Finally, 2 additional retrospective studies found the anterior approach to result in less PTPS.…”
Section: Surgical Factorsmentioning
confidence: 98%
“…Two retrospective studies found no difference between the classic posterolateral approach and the musclesparing posterolateral approach. 15,16 A subanalysis from a prospective study also found no difference in PTPS based on incision type. 17 Finally, 2 additional retrospective studies found the anterior approach to result in less PTPS.…”
Section: Surgical Factorsmentioning
confidence: 98%
“…In some publications, anterolateral thoracotomy and median sternotomy have been reported to cause less pain intensity than posterolateral thoracotomy. In order to prevent the development of PTPS, muscle sparing surgery was not found superior to posterolateral incisions [21,28].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Even muscle-sparing incisions appear to have no major advantage over posterolateral incisions (45). Overall, variation in surgical techniques has not been shown to reduce subsequent pain (46).…”
Section: Mechanism Of Post-thoracotomy Painmentioning
confidence: 99%